Corrigendum to "Local well-posedness and wave breaking results for periodic solutions of a shallow water equation for waves of moderate amplitude" [Nonlinear Anal. 97 (2014) 145–154]. (March 2020) - Mutlubaş, N. Duruk
Abstract: The local well-posedness of a periodic nonlinear equation for surface waves of moderate amplitude in shallow water was studied in Duruk Mutlubaş (2014) where an approach proposed by Kato based on semigroup theory for quasi-linear equations was used. It was also shown that singularities for the model equation can occur only in the form of wave breaking, in particular surging breakers. In this paper, we correct the mistake made in the proof of the main result on local well-posedness and give the appropriate assumptions followed by the corresponding results.